Peningkatan Pengetahuan dan Sikap Pencegahan Obesitas Melalui Emo- Demo di Puskesmas Lubuk Buaya - Dhafin Faiz Zaqi; Neni Fitra Hayati; Evi Maria Lestari Silaban; Erick Zicof; Nindy Audia (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Obesity is a condition characterized by excessive accumulation of body fat, resulting in a body weight far above normal, indicated by a BMI > 25. Data from Lubuk Buaya Public Health Center show that the prevalence of obesity has reached 10.2%. The low levels of community knowledge and attitudes toward obesity prevention are among the main contributing factors. One innovative educational method that can be applied is the Emo-Demo (Emotional Demonstration) method, which combines emotional and participatory approaches. Purpose: This study aimed to determine the improvement in community knowledge and attitudes regarding obesity prevention after being provided education using Emo-Demo media in the working area of Lubuk Buaya Public Health Center. Methods: This research used a mixed-method design with a quasi-experimental approach and an exploratory case study. A total of 70 respondents were selected using purposive sampling. Data were collected through in-depth interviews and questionnaires. Data analysis was performed using the Wilcoxon test. Results: The results of this study produced Emo-Demo educational media for community obesity prevention. The median knowledge score increased from 14.00 to 18.00, and the attitude score increased from 63.00 to 81.00 after the Emo-Demo education. Statistical tests showed a significant improvement (p-value 0,0001<0,05) in both knowledge and attitudes. Conclusion: In conclusion, there was an increase in community knowledge and attitudes regarding obesity prevention through Emo-Demo educational media in the working area of Lubuk Buaya Public Health Center, Padang. It is hoped that educational media using the Emo-Demo method can be further developed and utilized as an effort to prevent various diseases.